A aplicação do ensino híbrido na educação profissional e tecnológica: potencialidades e dificuldades - Antonello Neto, Alberto Pedro (2017)
This research was developed in the Post-Graduation Program in Professional and Technological Education of the Colégio Técnico Industrial of Santa Maria (PPGEPT - CTISM), Academic Master's Degree, in the line of research in Innovation for Professional and Technological Education. This study arose from the need to direct teaching to the needs of contemporary students, who are immersed in technology and yearn for differentiated teaching practices, aligned with the world of work. The objective of this study was to study the potentialities and difficulties of using this active methodology in EPT. It was proposed the application of the active methodology called Blended Learning (BL), in the models of Rotation by Stations and Flipped Classroom, in a discipline of the Technical Course in Environment, of the Colégio Politénico of Universidade Federal of Santa Maria. After the application of the models, two questionnaires of the semi structured type were distributed to the students, one at the end of each model, and at the end of the whole application, there was a semi structured interview with the titular teacher. The research was applied at the beginning of the academic semester of 2017, and the results indicated as greater potential the participation of the students, discussion of ideas and positions, previous preparation for the classes and optimization in the management of the time in the classroom; and how difficulties, problems in the technological resources and adequacy of the time the proposals, in the topics of the contents, go according to other researches that have been carried out. Due to the results, Blended Learning has great potential for application in EPT, however, infrastructure resources need to be resized to meet demand efficiently.